Industria de los cosméticos: tendencias de mercado de los biocosméticos - Aponte, Gloria María; Soledad-Rodríguez, Beatriz Elena; Delgado, Johana Emperatriz (Pontificia Universidad Católica del Perú, 2025)
Biocosmetics, products which utilize natural or biologically derived components, are gaining prominence due to their safety, sustainability, and effectiveness. Among their advantages are a lower risk of irritation and allergies, biodegradability, and applications in skincare, makeup, hair care, and perfumes. This study examines global market trends in the production and use of biocosmetics over the past decade, employing content analysis and a literature review of key market reports. The market is projected to reach $8.75 billion by 2032, with a compound annual growth rate (CAGR) estimated between 4.49% and 6.90% for the period 2019–2032. The findings highlight a transformation in the cosmetic industry, with biocosmetics emerging as a rapidly growing sector driven by increasing demand for safe, sustainable, and effective products

Los biocosméticos, productos que utilizan componentes naturales o de origen biológico, están ganando relevancia por su seguridad, sostenibilidad y efectividad. Entre sus ventajas destacan un menor riesgo de irritación y alergias, su biodegradabilidad y aplicaciones en cuidado cutáneo, maquillaje, cuidado capilar y perfumes. Este estudio analiza las tendencias globales del mercado en la producción y uso de biocosméticos en la última década, empleando análisis de contenido y revisión bibliográfica de los principales informes de mercado. Se estima que el mercado alcanzará los 8.75 mil millones de dólares para 2032, con una tasa de crecimiento anual compuesta (CAGR) proyectada entre 4.49% y 6.90% en el período 2019-2032. Los resultados evidencian una transformación en la industria cosmética, con los biocosméticos como un sector en rápido crecimiento, impulsado por la creciente demanda de productos seguros, sostenibles y eficaces.
Cosmetics industry: market trends of biocosmetics
Keywords: Biocosmetics; Market trends; Natural ingredients; Sustainability; Natural cosmetics; Tendencias de mercado; Biocosméticos; Ingredientes naturales; Sostenibilidad; Cosméticos naturales; https://purl.org/pe-repo/ocde/ford#1.04.00